Gender attitudes toward the physical module of program latihan khidmat negara (PLKN) : a study of PLKN'S trainees at Jugra Camp, Banting - Nurul Firdauz Abd Rahman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Understanding the application of the concept of equity is very crucial especially in educational course. In the case of physical education, equal opportunity in the sense of offering each student equal access to the programmes while ignoring individual differences is not an alternative in achieving gender equity. What is more appropriate is equality of outcome, which recognises that each student gets what is necessary to be educated. This study seeks to understand the module of PLK.N's physical activity with respect to trainees' perceptions toward the concept of equity in physical activity. The purpose of the study is to find out whether the physical module of PLK.N is seen as equitable by both genders. A stratified sampling has been applied whereby 160 PLK.N trainees at Jugra Camp Banting were given a questionnaire. The study employed an adapted version of Life Effectiveness Questionnaires which comprises seven dimensions (Neill et al., 2003). A total of 159 trainees responded, comprising a 99.4% return-rate. Quantitative analysis of the data was done using Statistical Package for the Social Sciences (SPSS). The quantitative findings of the study on the seven dimensions of Life Effectiveness Questionnaire show that no statistically significant difference exists between male and female trainees in the physical module with the exception on self-confidence and course values.